KEPUTUSAN PINDAH MEREK SMARTPHONE SAMSUNG KE XIAOMI MELALUI KETIDAKPUASAN KONSUMEN, REFERENCE GROUP DAN ELECTRONIC WORD OF MOUTH - Sunariani, Ni Nyoman; Arisandi, Thenia (Jurnal Ilmiah Manajemen & Bisnis, 2018)
Merk Switching Decision from Samsung to Xiaomi Smartphone Due To Costumers Dissatisfaction, Reference Group, and Electronic Word of Mouth. This research aims to analyze the effect of Consumer Dissatisfaction, Reference Group, and Electronic Word of Mouth (eWOM) on Brand Switching Decision from Samsung smartphone to Xiaomi. This is a quantitative research which relies on questionnaire as data collection method. There are 110 respondents which was taken using Accidental Sampling method as the samples. Testing method used in this research are as follow: Validation and Reliability test, Classic Assumption test, Multiple Linear Regression test, t-Test, F-Test, as well as Coefficient of Determination analysis which was processed using SPSS ver.17.0. The result of the research shows that the variable Consumer Dissatisfaction positively and significantly affecting Brand Switching Decision; Reference Group positively and significantly affecting Brand Switching Decision; and Electronic Word of Mouth (eWOM) positively and significantly affecting Brand Switching Decision. Consumer Dissatisfaction, Reference Group and Electronic Word of Mouth (eWOM) also positively and significantly affecting Brand Switching Decision from Samsung smartphone to Xiaomi simultaneously. As much as 71.0% of Brand Switching Decision was affected by Consumer Dissatisfaction, Reference Group, and Electronic Word of Mouth (eWOM), while the other 29.0% was affected by other factors which are not covered in this research.Keywords: Consumer dissatisfaction, reference group, electronic word of mouth, eWOM, brand switching decision, smartphone, Samsung, Xiaomi